QuerySheet: a bidirectional query environment for model-driven spreadsheets - Cunha, Jácome Miguel Costa (2013)
This paper presents a tool, named QUERYSHEET, to query spreadsheets. We defined a language to write the queries, which resembles SQL, the language to query databases. This allows to write queries which are more related to the spreadsheet content than with current approaches.